Two Cases of Late-Onset Anti-NMDAr Auto-Immune Encephalitis After Herpes Simplex Virus 1 Encephalitis - Dorcet, Guillaume; Benaiteau, Marie; Bost, Chloé; Mengelle, Catherine; Bonneville, Fabrice; Martin-Blondel, Guillaume; Pariente, Jérémie (Frontiers in Neurology, 2020)
CONTEXT: Meningoencephalitis due to herpes simplex virus 1 (HSV-1) was described as potential trigger for the development of anti-N-methyl-D-aspartate receptor (NMDAr) auto-immune encephalitis (AIE) in few days to few weeks after the infection. METHODS: Description of clinical, radiological and biological diagnoses process, treatment response, and evolution. The literature review was performed using Pubmed. CASES REPORTED: We report here cases of a 71-year-old man and a 57-year-old woman presenting anti-NMDAr AIE respectively twelve and seven months after HSV-1 meningoencephalitis. In both cases, the onset was brisk and the symptoms were mainly psychiatric (paranoid delirium, Capgras and Cotard syndromes) and cognitive, with anterograde amnesia. Relapse of HSV meningoencephalitis, epilepsy and paraneoplastic neurologic syndromes were excluded. The clinical response to the first-line treatment composed by intravenous immunoglobulin and high-dose corticosteroids was poor, whereas significant improvement was noticed after rituximab induction. CONCLUSION: Post-herpetic anti-NMDAr AIE could arise several months after infection. Clinicians must be aware of this possibility, particularly if cognitive and/or psychiatric symptoms occurred after a remitting period. In our two cases, only rituximab was associated with clinical improvement.